Welfare reforms from the perspective of the costing and distribution of benefits: a look at the totality (Revista do Tribunal Regional Federal da 3ª Região, 2013)
The aim of this essay is to present some reflections on past and future reforms of the pension system. Starting from a critical perspective of the reforms carried out so far, it is believed that it is not possible to present the issue clearly without a perspective of totality, that is, seeing the system as an integrated structure that must necessarily, analysis of fundraising and its distribution. In other words, no interpretation of the system can be detached from the funding and granting of benefits, and the aim is to demonstrate that partial views of these inseparable aspects have been responsible for the disorganization with which reforms have been carried out over the last twenty years, leaving us with a system that is always patched up and appears to be constantly being reformed. In order to achieve this goal, the article will begin by reviewing some historical aspects of the organization of the social security system that are decisive for the current organization of its funding and for the discussion on the existence or not of a social security deficit. Once this stage has been completed, it will be possible to briefly explore the discussion on the deficit, which is linked to the issue of popular acceptance and the political burdens of social security reforms. This will be followed by an analysis of some of the constitutional principles of social security that can help elucidate the issue. Once the content of the reforms of the 1990s has been presented, we will move on to the end of the article, where we will analyze their context in relation to the structure of the social security system and the economy, and present some suggestions for future reforms.
Keywords: social security; deficit; funding; reforms; principles; planning